Lobar versus sub-lobar surgery for pulmonary typical carcinoid, a population-based analysis - Furqan, Muhammad; Tien, Yu-Yu; Schroeder, Mary C.; Parekh, Kalpaj R.; Keech, John; Allen, Bryan G.; Thomas, Alexandra; Zhang, Jun; Clamon, Gerald; Hejleh, Taher Abu (Journal of Thoracic Disease, 2018)
Background: The optimal surgery for resectable pulmonary typical carcinoid (TC), e.g., lobar resection (L-R) vs. sub-lobar resection (SL-R), is controversial. This is further explored in this population-based study. Methods: The Surveillance, Epidemiology, and End Results (SEER) Program was used to select patients ≥66 years old, and diagnosed between 2000 and 2012 with pulmonary TC. A similar cohort was developed using the SEER-Medicare database (diagnosed from 2000−2007) to identify chemotherapy (CTX) use and co-morbidity. Five-year survival was calculated using univariate and multivariate analysis. Results: A total of 1,506 and 512 patients were identified from SEER and SEER-Medicare, respectively. In the SEER cohort, 49%, 29% and 21% received L-R, SL-R, and no surgery (NS), respectively. Those who received NS were older (P